The Effects of Nicotine on Histone Modifications in Carnorhabditis Elegans - Parker, Daniel H. (My University, 2017)
Early development stages have been known to be very susceptible to certain types of stress. Tobacco smoke is one of these major stresses that will affect them during this stage and can increase how likely they are to become smokers later. This is the problem that needs to be looked at as generations keep getting exposed to nicotine repeatedly potentially creating many epigenetic changes and creating a preference for nicotine over time. A lot of research has been done on how early nicotine exposure will affect you throughout the rest of your life and the transgenerational molecular mechanisms are still being researched today. In this study, we investigated the transgenerational effects of nicotine on H3K9 by testing the Spr-5 mutant and seeing it's chemotactic expressions compared to N2 (wild type) strain. The N2 strain expressed a preference for nicotine over multiple generations showing that nicotine preference or addiction can be passed down. When testing the Spr-5 strain which is missing an important histone in the germline dealing with epigenetic factors the preference is still passed down. This shows us that not all epigenetic activity is done in the germline and is done outside the germline as well. This study is trying to provide how nicotine effects histones and how this will be passed down through multiple generations. From this data, C. elegans may be a useful organism in testing the epigenetic factors of nicotine over time and identifying the molecular pathways of how this happens.
Keywords: Nicotine--Physiological effect; Caenorhabditis elegans; Histones; Molecular biology; Epigenetics